Heavy metal resistant bacteria from marine sediment of Pantai Balok, Pahang, Malaysia - Zainal Abidin, Zaima Azira; Haniff, Munira (Noor Publishing, 2020)
Heavy metal pollution particularly in the coastal water has become an issue of serious international concern. Heavy metal pollution not only affect the quality of water and soil, but it also affects the animals and plants as well as the microorganisms inhabiting the coastal area. This study aimed at isolation of heavy metal resistance bacteria from marine sediment of Pantai Balok as an attempt to assess possible heavy metal pollution present in that area as well as in search of potential candidates for bioremediation purposes. A total of 33 isolates were obtained and subjected for heavy metal resistance test using the following heavy metals - chromium (Cr), nickel (Ni), copper (Cu), cobalt (Co), cadmium (Cd). Results revealed that almost all isolates showed high tolerance towards Cr, Ni, Co and Cu but low tolerance towards Cd. Heavy metal resistance profile associated with Pantai Balok was in the following order: Cr > Ni > Co > Cu > Cd. Five isolates namely PB1, PB9, PB17, PB18, and PB 33 exhibited strong heavy metal resistance pattern and their identities were determined using 16S rRNA gene sequencing. PB1 was closely related to Stenotrophomonas maltophilia (99%) while PB9 to Staphylococcus pasteuri (98%). Isolates PB17 and PB18 were highly similar to Bacillus pumilus (99%) and Bacillus sp. (99%) respectively whereas PB33 is Pseudomonas aeruginosa (99%). The presence of heavy metal resistant bacteria may indicate the occurrence of heavy metal pollution in Pahang coastal water and may pose a potential health risk to the public.